(untitled) (Journal of Institute of Science and Technology, 2025)
A small system of typically 4–10 galaxies that appear to be isolated from other galaxies and situated very close to one another on the sky leading to tidal distortions, gas stripping and star bursts is called a Hickson Compact Group (HCG). We present a spectroscopic analysis of four member galaxies of HCG 7: NGC 192, NGC 196, NGC 197, and NGC 201, using data from the Sloan Digital Sky Survey (SDSS) Data Releases 12. Emission lines in the galaxy spectra are modeled with Gaussian profiles, and the Hα line is used to estimate Star Formation Rates (SFRs) and gas-phase metallicities. After extinction correction, we derive SFRs of 0.284 M☉/year, 0.222 M☉/year, and 0.034 M☉/year for the star-forming galaxies, NGC 192, NGC 201, and NGC 197, respectively with corresponding gas-phase metallicities (12 + log(O/H)) of 8.64 dex, 8.55 dex, and 8.56 dex. In contrast, NGC 196 shows no detectable Hα emission, consistent with a quiescent spectrum. The absence of a significant star-forming interstellar medium in NGC 196 may be attributable to environmental processes, with tidal stripping being the most probable quenching mechanism in the dense HCG 7 environment.